Personal characteristics and attitude toward knowledge sharing - Ida Juliana, Hutasuhut (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study attempts to look at knowledge management by taking individuals as the centre of attention. The individual as creator, custodian, sharer, manager and user of knowledge is a key determinant factor that ensures the success of knowledge sharing in organization, Therefore, there must be a reason behind the option of why they should share their knowledge. This study focuses on personality traits (conscientiousness, agreeableness, neuroticism, openness to experience and extraversion) of the individual with regard to his/her willingness to share knowledge. Although this is very important, unfortunately there are limited studies that examine personality traits toward knowledge sharing; The objective of this study is to examine whether there is a relationship between personality traits and attitude toward knowledge sharing. This study was conducted in University Malaysia Sarawak (Unimas). The unit of analysis is the lecturers from various faculties. A stratified random sampling method was used in the selection of respondents. There are 96 lecturers from various faculties that were selected for this study. Data was collected by using The Big Five Inventory (BFI) to examine the personality traits, and questionnaire to examine respondent's attitude toward knowledge sharing. The finding suggested that there is a positive and moderate relationship between personality and attitude toward knowledge sharing. Specifically, result on conscientiousness and agreeableness are positively and moderately related to attitude toward knowledge sharing. Result on openness to experience arjd-extraversion are positively and weakly related to attitude toward knowledge sharing. Finally result on neuroticism is negatively and weakly related to attitude toward knowledge sharing. It is expected that results from this study could contribute toward the literature on personality, knowledge management, HR practices (personnel selection or recruitment), training and team building in organization. The limitation, implication and recommendation for future study are also discussed.